Sisar model for Brazil rural water supply - Carvalho, Denise, (SAGE Business cases., 2020)
Brazil has problems typical of both rich and poor countries, such as urban air pollution, waste management issues and obesity, but also poverty, malnutrition and lack of access to clean water and sanitation. For over two decades, its northeastern state of Ceará experimented with a novel approach to providing affordable water and sanitation services to its impoverished rural population. The community service organisation SISAR, in partnership with various governmental institutions and development banks, managed to significantly increase rural coverage of clean water. Yet about half the population in rural Ceará still had no access to clean water supply or had precarious water services.